Аналіз змін у ядрах і функціональному стані тироцитів при пренатальній дії стафілококового анатоксину - Федосєєва, Ольга Віталіївна; Федосеева, О. В.; Fedosyeyeva, O. V. (My University, 2016)
У роботі представлений аналіз змін у ядрах і функціональному стані тироцитів щурів у постнатальному онтогенезі після пренатальної дії стафілококового анатоксину. Аналіз результатів з морфологічної та функціональної реорганізації ЩЗ дозволяє зробити висновок, що розвиток адаптаційно-компенсаторних процесів у щитоподібній залозі при внутрішньоутробній дії стафілококового анатоксину зачіпає всі структурні комплекси органу, проявляється мозаїчно, що обумовлено принципом тимчасової переміжної активності функціонуючих структур. Виявлені морфологічні перебудови свідчать про гіпофункціональний стан органу. Зміни ядерцевого апарату з боку тироцитів великих фолікулів свідчать про пригнічення синтезу та двостороннього виведення активних продуктів структурами щитоподібної залози. В работе представлен анализ изменений в ядрах и функциональном состоянии тироцитов щитовидной железы крыс в постнатальном онтогенезе после пренатального воздействия стафилококкового анатоксина. Анализ результатов морфологической и функциональной реорганизации щитовидной железы позволяет сделать вывод, что развитие адаптационно-компенсаторных процессов в щитовидной железе при внутриутробном действии стафилококкового анатоксина затрагивает все структурные компоненты органа, проявляется мозаично, что обусловлено принципом временной перемежающейся активности функционирующих структур. Обнаруженные морфологические перестройки свидетельствуют о гипофункциональном состояние органа. Изменения ядрышкового аппарата со стороны тироцитов крупных фолликулов свидетель- ствуют об угнетении синтеза и двустороннего вывода активных продуктов структурами щитовидной железы. There have been many reports on the morphology of the thyroid gland. Inasmuch as, unlike the other endocrine organs, the thyroid gland stores its secretion in the follicles, and discharge of the follicular content into the circulation is an independent process and is not synchronous with the production and secretion of that content into the follicles, its morphologic features are poorly independent in level of the functional activity. Evidence in imaging role of the lymphocytes such as factor of morphogenesis are not clarify understood. Based on previous researches that intrauterine antigen influence causing the undifferentiated cytotoxic T-lymphocytes’ premature migration from thymus to the peripheral organs was decided to investigate the rat’s thyroid gland at various age periods. As a material for the research was thyroid glands of Wistar rats aged 1 to 45 days of postnatal development (126 animals). Studied three groups of animals at 1, 3, 7, 11, 14, 21, 45 days: I group – intact animals (normal): 42 rats; II group – control, animals which were intrafetal injected by 0.9% solution of NaCl; III – experimental, animals which were intrafetal injected by staphylococcal toxoid adsorbed purified liquid (10-14 units in 1 ml binding diluted 10 times) on 18 days of pregnancy. Thyroid were fixed in 10% neutral formalin solution. Objects embedded in paraffin blocks by conventional method. Histological sections of 3-5 microns thick were stained by hematoxylineosin and by histochemical methods (reaction by Brás, PAS-reaction, AgNOR’s). In the article was analyzed the changes in the nuclei and functional status of thyrocytes of rats in postnatal ontogenesis after prenatal action of staphylococcal toxoid. This reaserch proved that the intrauterine action of staphylococcal toxoid causes a decrease in the average diameter of the nuclei of thyrocytes in rat of early milk period, compared with the control group. There is a tendency to reduce the number of nucleoli in thyrocytes of large follicles and an increase in adenomeres of medium and small diameters. Reducing the number of nucleoli in follicular endocrinocytes indicates a decrease in the synthesis of ribosomal subunits, and consequently the gross fusion protein products, accompanied by a slowdown in output of hormones into the bloodstream (there are absent vacuoles of resorbtion in colloids). Stagnation of a secret of follicles cavity causes it to stretch the walls, causing the symptoms of hypertrophy. Analysis of the results of morphological and functional reorganization of the thyroid gland leads to the conclusion that the development of adaptive-compensatory processes in the thyroid gland after intrauterine staphylococcal toxoid action affects all structural complexes body appears mosaic, due to the principle of temporary intermittent activity of functional structures. The observed morphological reconstruction indicate of hypofunctional status of thyroid. Changes in nucleolar apparatus of thyrocytes of large follicles indicate that inhibition of the synthesis and bilateral output of active products in thyroid.
Анализ изменений в ядрах и функциональном состоянии тироцитов при прена¬тальном действии стафилококкового анатоксина
Analysis of changes in the nuclei and functional status of thyrocytes after prenatal action of staphylococcal toxoid
Keywords: щитоподібна залоза; щури; стафілококовий анатоксин; щитовидная железа; крысы; стафилококковый анатоксин; thyroid gland; rates; staphylococcal toxoid